PENGARUH KEBIASAAN BELAJAR DAN LINGKUNGAN KELUARGA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA - Riskyka (Jurnal Sintaksis, 2021)
The purpose of this study was to determine how study habits affect student learning outcomes in mathematics subjects at Al Maksum Stabat Private Junior High School, to find out how the family environment affects student learning outcomes in mathematics subjects at Al Maksum Private Junior High School Stabat, and to determine the effect of study habits. students and the family environment on student learning outcomes in mathematics at Al Maksum Stabat Private Junior High School. The population in this study were all eighth grade students of Al Maksum Stabat Private Junior High School, 98 students. Then 2 classes were selected from 3 classes. Data collection techniques in the form of observation, and questionnaires. The data analysis method used is multiple linear regression analysis using the SPSS program. The results showed that the significant value of study habits had an average value (M) of 36.63 which was in the 34-41 interval with the "Good" category. The family environment had an average value (M) of 36.84 which was in the interval 34-41 with the category "Good". While learning skills and family environment on student learning outcomes in mathematics subjects at Al Maksum Private Junior High School Stabat. This is indicated by the calculated F value of 15.300 < from the F table with a significant level of 0.000 <0.05. While the results of the calculation of the coefficient of determination (R2) of 0.342, which means that 34.2% of student learning outcomes are influenced by the variables of study habits and family environment, while the other 69.8% are influenced by other factors not discussed in this study.